KSPN strategy in supporting economic growth or making socio-ecological crisis? - Aviliani, Aviliani; Herawan, Jonathan; Parningotan, Firman (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2024)
This research was conducted to analyze the development of the National Tourism Strategic Area (KSPN) contained in PERPRES 109/2020 and PERPRES 3/2016 concerning the Acceleration of Implementation of National Strategic Projects. The KSPN development in the concept of 10 new Bali but the problem is that some of the KSPN developments are located in environmental conservation areas. This research will look at the interlinkage, income impact, and labor impact of the KSPN construction using the 2016 Interregional Regional Input-Output (IRIO) tables obtained from Badan Pusat Statistik (BPS) RI and using project value calculation scenarios from KSPN whose data were obtained from the KPPIP. The results of this study indicate that on the Degree of Sensitivity Index (IDK) the dam processing industry sector, the electricity and gas procurement sector is a sector with strong values, but in a linear the air procurement, waste management, waste and recycling sectors are sectors that have no impact from the KSPN. In the Degree of Distribution Index for the electricity and gas procurement sector, the sector with the largest spread of values for weak sector results varies. The results of the Income Impact analysis show that the wholesale and retail trade sectors; car and motorbike repairs as well as the processing industry, while the air supply sector, waste management, waste and recycling are sectors with a small income impact and also have an impact on employment on several islands in Indonesia. The Agriculture, Forestry and Fisheries sectors are the sectors with the strongest employment impact on the islands of Sumatra and Kalimantan due to the existence of KSPN. The recommendation from this research is that there is a need for government evaluation, especially in selecting KSPN in environmental conservation areas as well as development in the circular economy infrastructure concept.